2023
DOI: 10.1039/d3ra03871h
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the synthetic strategies of benzoxazoles using 2-aminophenol as a precursor: an up-to-date review

Abstract: Benzoxazole is a resourceful and important member of the heteroarenes that connects synthetic organic chemistry to medicinal, pharmaceutical, and industrial areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 84 publications
(105 reference statements)
0
12
0
Order By: Relevance
“…The solid so formed was collected through decantation followed by washing with cold alcohol and dried under vacuum. The dried sample showed following spectral data: δ 10.44 ppm (1H, D 2 O exchangeable), 12 numbers of aromatic protons and δ 5.40 ppm a methine proton in its 1 H NMR spectra; in 13 C NMR spectra it shows altogether 25 signals among which only one is aliphatic carbon (methine). These NMR data indicated that the product can be either 4 a or 5 a.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The solid so formed was collected through decantation followed by washing with cold alcohol and dried under vacuum. The dried sample showed following spectral data: δ 10.44 ppm (1H, D 2 O exchangeable), 12 numbers of aromatic protons and δ 5.40 ppm a methine proton in its 1 H NMR spectra; in 13 C NMR spectra it shows altogether 25 signals among which only one is aliphatic carbon (methine). These NMR data indicated that the product can be either 4 a or 5 a.…”
Section: Resultsmentioning
confidence: 95%
“…The hydroxy aldehydes bearing tert-butyl group prepared by Duff's formylation method from 4-tert butyl phenol and coumarin moiety prepared from 4-methyl/phenyl 7-hydroxy coumarin via Duff's method [31] all reacted in a similar fashion (Figure 5, 5 n-p) albeit moderate yield in some cases. The identity of all the products (5 c-p) were verified by their 1 H, 13 C NMR spectra and HRMS analyses (ESI).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…44–47 The coupling of aldehyde and aminophenol, used as a model reaction in many benzoxazole studies, represents a strategy for synthesizing benzoxazole from a simple molecular structure without the need to synthesize a specific precursor. 48 Han et al demonstrated the oxidative cyclization of aldehydes with aminophenols using methoxy-functionalized TEMPO (Scheme 1a), 49 while Wang et al employed MOFs as the primary metal catalyst in combination with molecular TEMPO (in homogeneous media) as a co-catalyst for this reaction (Scheme 1b). 50 Although both studies utilized catalytic amounts of TEMPO derivatives, the TEMPO radicals were not recovered or recycled after the main reaction.…”
Section: Introductionmentioning
confidence: 99%